EVALUATION OF THE SOCIAL REHABILITATION PROGRAM FOR UNFITABLE HOUSES (RS-RTLH) IN CIKEMBAR DISTRICT SUKABUMI DISTRICT - Yobi Stiawan; Andi Mulyadi; Yana Fajar FY Basori (DIA: Jurnal Administrasi Publik, 2023)
The title of this study is "Evaluation of the Social Rehabilitation Program for Uninhabitable Houses in Cikembar District, Sukabumi Regency".This study aimed to evaluate the Social Rehabilitation Program for Uninhabitable Houses in Cikembar District, Sukabumi Regency, to identify the inhibiting and supporting factors of this program. This study uses a qualitative research method with a narrative approach. Data collection techniques include observation, interviews, and documentation. The results of this study indicate that. The effectiveness of RTLH rehabilitation in Cikembar District, has been effectively carried out by the Housing and Settlement Service of Sukabumi Regency, Sufficiency in implementing RTLH rehabilitation is provided to low-income communities, Equitable rehabilitation of RTLH is provided to communities according to the criteria in Sukabumi Regent Regulation Number 46 of 2019. Responsiveness to the people whose houses have been rehabilitated is satisfied with government assistance. Accuracy is good and right on target. Inhibiting factors are insufficient budget, determination of low-quality materials, and lack of mutual cooperation in the community. While the supporting factors are the involvement of the community, RT, RW, Kelurahan,